THE ROLE OF ORGANIZATIONAL CULTURE MEDIATOR IN THE EFFECT OF KNOWLEDGE MANAGEMENT ON EMPOWERMENT AND ORGANIZATIONAL ENTREPRENEURSHIP IN SPORT ORGANIZATIONS’ EMPLOYEES - Mohsen Taybi; Majid Keramati Moghaddam (Sport Scientific And Practical Aspects, 2025)
The present study aims to investigate the role of organizational culture mediator in the effect of knowledge management on empowerment and organizational entrepreneurship in sport organizations’ employees. Statistics population includes all employees of Esfahan’s sport boards that was selected 234 people according to Kerjcie and Morgan table as sample; but for insuring the results of data analyzing and suitable popularization, 300 questionnaires were distributed and collected 274 acceptable questionnaire. The instruments used to collect the data include Lawson (knowledge management standard questionnaire; Spritzer organizational entrepreneurship standard questionnaire; Rezaie empowerment standard questionnaire; and Robbins organizational culture standard questionnaire. Results of the study revealed that knowledge management has positive significant effects on empowerment (0.39), organizational culture (0.78), and organizational entrepreneurship (0.18) in employees of Esfahan’s sport boards. Also in the indirect way, knowledge management variable on employee’s empowerment according to organizational culture mediator with 0.50 coefficient, and knowledge management variable on organizational entrepreneurship according to organizational culture mediator with 0.73 coefficient has positive significant effects